2015
DOI: 10.1136/bmj.h5087
|View full text |Cite
|
Sign up to set email alerts
|

Slow and costly access to anonymised patient data impedes academic research

Abstract: Getting data from the Health and Social Care Information Centre in England is time consuming and expensive—and Jonathan Filippon is still waiting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…It has been suggested that NHSD, which performed the linkage to HES for our study, was overwhelmed with data linkage applications. 24 This may limit the usefulness of administrative data in trials with funder-imposed deadlines for completion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that NHSD, which performed the linkage to HES for our study, was overwhelmed with data linkage applications. 24 This may limit the usefulness of administrative data in trials with funder-imposed deadlines for completion.…”
Section: Discussionmentioning
confidence: 99%
“…We identified several publications which aimed to provide a firsthand description of specific data sharing experiences [16,23,143,[195][196][197]. For example, Savage and Vickers obtained only one of 10 requested studies and established contact with only five of 10 corresponding authors [196].…”
Section: Relation To Other Studiesmentioning
confidence: 99%
“…Barriers to accessing data were similar to those we describe here and included difficulties establishing contact with study authors, denial of requests for raw datasets because of ongoing analysis or because of a lack of time and personnel to properly prepare data. Geifman et al and Filippon et al reported costly and repeated data sharing requests [143,197]. Nevitt et al performed a systematic review of IPDMAs published between 1987 and 2015, and reported that only 25% of published IPDMAs had access to all identified IPD and no improvement in data retrieval rate over time [16].…”
Section: Relation To Other Studiesmentioning
confidence: 99%
“…Access to data through NHS Digital has been perceived as slow and costly, 40 with detailed attention to legal basis, information governance and fair processing. In our experience, many researchers opt to develop separate data-sharing agreements with providers outside of NHS Digital to avoid the DARS process.…”
Section: Nhs Digitalmentioning
confidence: 99%